COVID-19 vaccine race – the shadow of political and multinational interests - Daniel Rajmil; Lucía Morales; Toni Aira (Cogent Social Sciences, 2024)
The COVID-19 pandemic caused global disruption in 2020, throwing the world into an unprecedented health crisis with unpredicted socio-economic consequences. Strikingly, politicians and supranational organizations failed to collaborate and coordinate a united global response. In light of this, this research study explores how the vaccine race may have been used as a weapon of political communication, constantly influenced by international relations and economic interests. This study analyses the US response to the COVID-19 pandemic and how the vaccine development was used to support Trump’s political discourse to gain international political leadership amidst the electoral campaign to become reelected. The core research findings show that President Trump’s administration started politicizing vaccine developments as the country became immersed in the 2020 presidential campaign. Furthermore, the reviewed literature and the empirical evidence suggest that advancements in the country’s pharmaceutical sector and the development of the COVID-19 vaccine were used as a communication weapon to affect Trump’s political campaign and the global COVID-19 vaccine race.